EFFECTS OF DIFFERENT GROWING MEDIA ON SCOTCH PINE (PINUS SYLVESTRIS) PRODUCTION - M. Aklibasinda; T. Tunc Y. Bulut; U. Sahin (Journal of Animal and Plant Sciences, 2011)
Scotch pine is the most extensively planted pine in the world due to it has high economic value. Scotch pine seedlings are produced from seeds. This study was carried out to determine the effects of different growing media on Scotch pine (Pinus sylvestris) seedling growth attributes such as collar diameter, seedling length, root length, the number of roots, fresh and dry root weight and fresh and dry seedling weight. Eighteen different media were experimented by using rice hulls, pumice and peat materials alone or mixing two of them. The water retention characteristics of each media was also determined and used to obtain pore size distribution, aeration and water retention. The results indicated that growing media had significant effects on plant production parameters. The highest seedling growth attributes were obtained from the media prepared by adding 10% rice hulls to peat material. Aeration porosity and usable water amount as volume of this media was 60.1% and 15.9%, respectively. Among the pure media, it was found that seedling could not grow in pure rice hulls media. It was observed that adding rice hulls material up to 30% to peat material almost gave same results by using peat alone as a media.
Keywords: pine production; growing media; water retention; aeration.